Binder‐Free Electrodes with High Energy Density and Excellent Flexibility Enabled by Hierarchical Configuration for Wearable Lithium Ion Batteries. Issue 8 (28th May 2021) - Li, Shaoqing; Zhou, Weiya; Xia, Xiaogang; Lu, Zhao; Chen, Penghui; Wang, Zibo; Xiao, Zhuojian; Xi, Wei; Wang, Yanchun; Rao, Guanghui; Xie, Sishen
Abstract: There is strong demand for higher energy density and flexible lithium ion batteries recently. Unfortunately, electrodes built by conventional methods cannot meet these requirements simultaneously due to the large amount of inactive additives needed for sufficient flexibility. Herein, by utilizing a continuous single‐walled carbon nanotube reticulation and designing an all‐in‐one hierarchical configuration, binder‐free electrodes are fabricated via an in situ integration procedure. The electrode exhibits excellent electrochemical performance against up to 20 000 cycles of bending and high energy density (up to 493 Wh kg −1 electrode and 820 Wh L −1 electrode ). The hierarchical configuration takes full diverse advantages of different carbon nanostructures. The as‐obtained novel binder‐free electrodes exhibit not only good cyclability (up to ≈90% capacity retentions after 1500 cycles) with only 4 wt% additive materials, but also show enhanced kinetic process, in comparison to those of traditional electrodes. Furthermore, based on the as‐designed electrodes, flexible cells are assembled and a practical wearable system is fabricated, manifesting that they can be used in a stable and flexible power supply for smart systems. Abstract : A freestanding and binder‐free electrode with an integrated hierarchical configuration is fabricated for flexible lithium ion batteries. In this ingenious design, different carbon nanomaterials with different macroscopic structures serve diverse functions by exerting their respective advantages. The as‐obtained electrodes exhibit an excellent flexibility and high energy density simultaneously, showing great potential in the application of next generation wearable electronics.